2022
DOI: 10.1007/s00520-022-07547-9
|View full text |Cite
|
Sign up to set email alerts
|

Implementing a web-based system of screening for symptoms and needs using patient-reported outcomes in people with cancer

Abstract: Purpose To evaluate the implementation of a web-based system of screening for symptoms and needs in people with diverse cancers in a general hospital in Australia. Methods This was a prospective, single-arm, pragmatic intervention study. After local adaptation of an online portal and training, cancer nurses were asked to register patients to screen via the portal in clinic or at home. Symptoms were scored according to severity, and scores above cut-off were reported to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Sixty‐nine percent of the remaining distress‐symptomatic patients accepted onward referral to community‐based psychosocial support services, one fifth of all screened patients, all of whom received some form of intervention, mostly low‐cost psycho‐educational advice. The 80% acceptance of SDS was higher than other reported studies using ESAS; a 70% screening rate reported in an Ontario province‐wide study, 23,24 77% reported in another Canadian study focusing on advanced cancer 25 and 69% reported in an Australia general hospital 20 . Evidence suggests that implementation strategies could improve the screening rate to >90% 26 …”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Sixty‐nine percent of the remaining distress‐symptomatic patients accepted onward referral to community‐based psychosocial support services, one fifth of all screened patients, all of whom received some form of intervention, mostly low‐cost psycho‐educational advice. The 80% acceptance of SDS was higher than other reported studies using ESAS; a 70% screening rate reported in an Ontario province‐wide study, 23,24 77% reported in another Canadian study focusing on advanced cancer 25 and 69% reported in an Australia general hospital 20 . Evidence suggests that implementation strategies could improve the screening rate to >90% 26 …”
Section: Discussionmentioning
confidence: 81%
“…The 80% acceptance of SDS was higher than other reported studies using ESAS; a 70% screening rate reported in an Ontario province-wide study, 23,24 77% reported in another Canadian study focusing on advanced cancer 25 and 69% reported in an Australia general hospital. 20 Evidence suggests that implementation strategies could improve the screening rate to >90%. 26 One in three patients screened reported moderate-to-severe symptom distress, at the lower end of the 30%-50% range reported in previous cancer SDS studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations